Total Petroleum Hydrocarbons and their relationship with Total Organic Carbon in the sediment from the Northern Part of Shatt Al-Arab River Basrah – Iraq - Al-Hajaj et al. (Iraqi Journal of Aquaculture, 2025)
The current study deals with the concentrations of total petroleum hydrocarbons (TPH) and determination of the percentage of total organic carbon (TOC) and the texture components in the sediments of five stations selected in the northern part of Shatt Al-Arab River (Al-Qurna, Al-Sharish, Al-Shafi, Al-Deir and Al-Hartha) during the period from 2018 to 2019. The concentrations of TPH in the sediments were estimated using a fluorescence device. The lowest concentration was 7.933 μg/g dry weight at Al-Shafi station during the summer while the highest was 52.793 μg/g dry weight at Al-Deir station during the winter. The percentage of TOC content in the sediments ranged between 5.754% and 15.612%. It was noted that the texture of the sediments was of the silty clay type, and the average percentage of clay was 27.6%, silt (64.2%) and sand (8.2%). Statistical analysis showed positive correlations between both TPH and TOC in the sediments.